Effect of subchronic exposure to manganese on mineral metabolism in Wistar rats - T. V. Kazakova; O. V. Marshinskaia; S. V. Notova (Acta Biomedica Scientifica, 2024)
Background. The presence of increased manganese concentrations in soils and water intakes areas for drinking and household purposes in a number of the Russian Federation subjects indicates the  chronic influence of this metal on all segments of the population. This situation is aggravated by violation of the optimal nutrition principles, which leads to changes in the organism absorption of micronutrients. In this regard, the study of the elemental status of an organism against the background of manganese exposure is of particular importance.The aim. To study the effects of subchronic exposure to manganese on the mineral status of Wistar rats.Materials and methods. To  conduct the study, 20  mature rats were selected, from which two groups were formed – control (n = 10) and experimental (n = 10). Animals in the control group received a general diet, animals in the experimental group received a diet with additional administration of manganese sulfate at a dose of 1433 mg/kg for 28 days. At the end of the preparatory period, blood and brain samples were taken to determine the content of chemical elements using inductively coupled plasma mass spectrometry and of metal-ligand manganese forms using high-performance liquid chromatography combined with inductively coupled plasma mass spectrometry.Results. It has been established that subchronic oral exposure to manganese leads to an increase in the content of this microelement in the blood serum and to a decrease in the levels of calcium, potassium, magnesium, iron and copper. In the cerebral cortex, the level of manganese, lead, mercury and strontium increases against the background of a decrease in iron and iodine levels. An increase in the gross content of manganese in blood serum leads to an overload of the main high-molecular carriers and initiates the formation of low-molecular forms of manganese.Conclusion. Subchronic oral exposure to manganese leads to the accumulation of this microelement in the body of animals and to the development of an imbalance of a number of macro- and microelements.